Supramolecular Complexes of 3-Epi-2-deoxyecdysone with Cyclodextrins and Their Anti-Inflammatory Activity - Temirgaziev, B. S.; Tuleuov, B. I.; Romanova, M. A.; Seidakhmetova, R. B.; Seilkhanov, T. M.; Seilkhanov, O. T.; Salkeeva, L. K.; Adekenov, S. M. (Russian Journal of General Chemistry, 2019)
The ecdysteroid 3-epi-2-deoxyecdysone has been isolated from the aerial part of Acanthophyllum gypsophiloides Regel. The complexes formation of the ecdysteroid with α-, β-, γ-, and 2-hydroxypropyl-β-cyclodextrins has been studied by means of NMR spectroscopy. Anti-inflammatory activity of the obtained 3-epi-2-deoxyecdysone complexes with cyclodextrins has been investigated.
Keywords: 3-epi-2-deoxyecdysone; cyclodextrins; supramolecular complexes; inclusion complexes